Upaya Pemenuhan Hak Pendidikan Anak Melalui Kelompok Belajar “Perwira” Di Gang Perwira Medan - Wanur Dillah; Mia Aulina Lubis (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Education is an effort and effort to make individuals or groups understand their potential through teaching and training. Through education the attitudes and behavior of a person or group of people are more focused, disciplined and accountable. Education is divided into three channels, namely formal education, informal education and non-formal education. Gang Perwira is one of the many areas with middle to lower economy in Medan City. The purpose of this Study Group or Pursuit is as an initial approach that is carried out by the practitioner with Gg Perwira' children as well as a mini project treatment. This Study Group is also an effort to fulfill the rights of Gg Perwira' children in the field of education. Using the Casework method (Individual Intervention) according to Skidmore, namely: 1). Study Phase, 2) Assessment Phase, 3) Intervention, and 4) Termination. Various creativity programs have been implemented such as making origami, coloring, drawing and making traditional engrang shell toys. Reinforcing is anything that increases the likelihood of a certain behavior occurring. If this method is successful, it is likely that the child will have the expected behavior. The hope is that Gg Perwira's children are always motivated and their interest in learning is maintained.